Bibliometric Analysis of Parental Mediation, Screen Time, and Digital Media in Early Childhood (2021–2026) - Athira Nur Fairisha; Rahmah Rahmah (Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of digital technology has increased digital media use and screen time among young children, particularly during and after the COVID-19 pandemic. This condition has driven growing research interest in parental mediation, digital parenting, and the impact of digital media on child development. The present study aims to analyze publication trends, research theme development, most influential articles, and future directions related to parental mediation, screen time, and digital media among children, preschool children, and toddlers during the period 2021–2026. This study employed bibliometric analysis using data sourced from the Scopus database. Data analysis was conducted with VOSviewer to visualize the keyword co-occurrence network, overlay, and density visualizations. The findings show that publications related to screen time and digital media increased significantly during 2021–2026. Research themes were dominated by screen time, digital media, mental health, sleep, emotional wellbeing, behavioral problems, and parental mediation. Furthermore, recent developments indicate a shift in focus from screen exposure toward psychosocial aspects, digital parenting, emotional regulation, and behavioral outcomes in early childhood. This study demonstrates that research on digital media use in children has evolved into a multidisciplinary field encompassing health, psychology, education, behavioral sciences, and public health. The results provide a comprehensive overview of global research trends and highlight the growing importance of digital parenting and psychosocial outcomes in early childhood digital media use. Keywords: parental mediation; screen time; digital media; children; bibliometric analysis, Scopus; VOSviewer